Termite mushrooms (Termitomyces) in Nepal: Exploring its distribution and diversity across ecological gradients - Aryal, Hari Prasad (Nepal Journal of Botany, 2024)
The distribution and diversity of Termitomyces were studied along three different ecological zones within three phytogeographic divisions. The main aim of the study is to assess patterns of species diversity and distribution along the east-west and south-north gradients of Nepal Himalaya. Soil samples from 27 locations were collected; among them four different types of soil (i.e. termite nest, casing soil, vicinity area and forest soil) were fixed for each spot to observe nutrient status of soil and influence of surrounding soil nutrients in the growth of T. albuminosus. In total, nineteen taxa have been recorded excluding non-termite mushrooms. The study revealed that species richness was significantly variable within physiographic region, land use, locality, altitude and air temperature for the distribution of Termitomyces. Analysis of soil nutrients (N, P, K, OM, Fe, Zn, Cu, Mn and B) revealed that the presences of organic matter and microelement content was apparently higher in most of the natural protected forest with comparisons to the agro-pastoral, plantation and managed forest. Most of the nutrients and their interaction between soil source and eco-zone were significantly different at p < 0.05. The study observed that the organic matter content was highest in the Tarai (5.40%) in termite nest (7.90%), comparative to the lowest contain of 2.47% in the Midhill regions of casing soil (1.38%). The study observed that biomass yield of T. albuminosus was highest in Tarai, followed by the Siwalik and Mid-hill regions.